Assessment and comparison of the levels of N-nitrosonornicotine and 4-(n-methyl-n –nitrosamino) -1-(3-pyridyl)-1-butanone in the saliva of tobacco chewers and non- chewers -a hospital based study - Harpreet Kaur Gandhoke, Dr; Vasanti Lagali Jirge, Dr; Anjana Bagewadi, Dr (International Journal of Dental Research, 2018)
Background: Studies estimating the Tobacco- specific nitrosamines, (TSNA’s) which are the strongest carcinogens in the saliva oftobacco users and tobacco quitters, are limited.Objectives: To assess and compare the levels of N- nitrosamines (NNN, NNK) in the saliva of tobacco chewers and non -chewers including those who have quit the habit of tobacco use.Methods: The study included 120 patients who were divided into three groups of 40 each: Group I- Smokeless tobacco chewersGroup II- Tobacco chewers who have completely stopped the habit at least 2 weeks prior to sample collection andGroup III- non-chewers. The salivary levels of two tobacco specific nitrosamines; NNN & NNK levels were estimated in the three study groups. Statistical analysis was done by Kruskal– Wallis, one-way analysis of variance (ANOVA) test, Mann-Whitney U test. (p-value < 0.05 was considered to be statistically significant)Results: In Group I, the mean level of NNN was 651.84 ± 359.78 and mean level of NNK was 168.32 ± 131.83. In Group II, the mean level of NNN was 119.52 ± 95.05 and mean level of NNK was 42.78 ± 43.19. In Group III, the mean level of NNN was 3.44 ±6.55 and mean level of NNK was 1.98 ± 3.68. There was a statistical difference in the 3 groups with respect to mean levels of NNN and NNK.Conclusion: The study indicated that salivary tobacco-specific nitrosamines are elevated in tobacco chewers. Saliva can be used to detect TSNA’s and screen for TSNA’s during each patient’s de-addiction process.